Analisis Pengaruh Upah, Modal, dan Nilai Produksi terhadap Penyerapan Tenaga Kerja di Industri Tahu Serasi Kecamatan Bandungan - Dian Widya Nugrahaeni; Herniwati Retno Handayani (Diponegoro Journal of Economics, 2020)
The industrial sector be able to lead the other sectors in an economy towards advancement. Indonesia focused on small industries because greatly contribute to job creation. Tahu Serasi Kecamatan Bandungan Industry is one of the small industries that has the potential to absorb the labor. The purpose of this study was to determine the effect of wages, capital, and value of production on the reqruitment of worker in Tahu Serasi Kecamatan Bandungan Industry. This research was conducted to 31 entrepreneurs who owned the Tahu Serasi Kecamatan Bandungan Industry which using census techniques. The data in this study are primary data taken using the interview method guided by a questionnaire and secondary data obtained by the literature method. The analytical method used in this study is multiple linear regression analysis with SPSS 23 for Windows. The results of this study indicate that the variable wages (X1) and capital (X2) have a positive and significant effect on employment in the Tahu Serasi Kecamatan Bandungan Industry. While the variable production value (X3) has a negative and significant effect on the reqruitment of worker in the Tahu Serasi Kecamatan Bandungan Industry.